Polymorphisms in alternative oxidase genes from ecotypes of Arabidopsis and rice revealed an environment‐induced linkage to altitude and rainfall. Issue 1 (24th January 2023) - Thiers, Karine Leitão Lima; da Silva, João Hermínio Martins; Vasconcelos, Disraeli Cavalcante Araújo; Aziz, Shahid; Noceda, Carlos; Arnholdt‐Schmitt, Birgit; Costa, José Hélio
Abstract: We investigated SNPs in alternative oxidase (AOX) genes and their connection to ecotype origins (climate, altitude, and rainfall) by using genomic data sets of Arabidopsis and rice populations from 1190 and 90 ecotypes, respectively. Parameters were defined to detect non‐synonymous SNPs in the AOX ORF, which revealed amino acid (AA) changes in AOX1c, AOX1d, and AOX2 from Arabidopsis and AOX1c from rice in comparison to AOX references from Columbia‐0 and Japonica ecotypes, respectively. Among these AA changes, Arabidopsis AOX1c_A161E&G165R and AOX1c_R242S revealed a link to high rainfall and high altitude, respectively, while all other changes in Arabidopsis and rice AOX was connected to high altitude and rainfall. Comparative 3D modeling showed that all mutant AOX presented structural differences in relation to the respective references. Molecular docking analysis uncovered lower binding affinity values between AOX and the substrate ubiquinol for most of the identified structures compared to their reference, indicating better enzyme‐substrate binding affinities. Thus, our in silico data suggest that the majority of the AA changes found in the available ecotypes will confer better enzyme‐subtract interactions and thus indicate environment‐related, more efficient AOX activity.